In Vivo and In Silico Pharmacokinetics Studies on Coumarinolignoid Cliv-92: Unraveling its Effect on Rifampicin-Induced Hepatic Damage - Kumar, Ajay; Alam, Sarfaraz; Tandon, Sudeep; Shanker, Karuna; Khan, Feroz; Saikia, Dharmendra (Current Topics in Medicinal Chemistry, 2025)
Background Drug-induced hepatotoxicity is a major concern and is caused by all classes of medications, indicating a key area of research. Antitubercular drugs have a beneficial effect but cause hepatotoxicity on prolonged use. Aim The present work aimed to investigate the role of rifampicin-induced hepatic damage and the effect of Cliv-92 on rifampicin-induced alteration in rats. Methods Rats were administered with rifampicin, Cliv-92, and silymarin (standard) orally in 0.5% carboxymethyl cellulose (CMC) suspension, in doses of 100 mg/kg, once daily for fourteen days, one hour before the administration of rifampicin. Control animals were treated with 0.5% CMC. On the 14th day, 1hr after the last drug administration, tissue was collected, homogenized, and various parameters, viz. SOD, CAT, GPX, and cytochromes, were estimated from rat liver supernatant and compared with the control group. Blood serum parameters were also measured. Simultaneously, antioxidant activity and in silico studies were performed. The constituent isoforms of Cliv-92 and silymarin and their metabolites were analyzed for different pharmacokinetic characteristics. Silymarin was used as a standard drug. Results The result of the study suggests that the hepatoprotective potential of Cliv-92 is due to its antioxidant property and inhibitory effect on hepatoproteins, cytochromes (CPY450). An in-silico finding validates the safety profile of Cliv-92, its metabolites, and the standard drug silymarin and also explains that the drug is non-mutagenic. Conclusion The result of this study indicated that both Cliv-92 and silymarin could be used to avoid drug-induced overload and hepatic damage.
Keywords: cytochrome P-450